Pengembangan Milk Tea Boba Ikan Nila Rumput Laut pada Kelompok Usaha Conac Snacks and Drinks Banjarbaru: Development of Milk Tea Boba Tilapia Seaweed in Conac Snacks and Drinks Banjarbaru Business Group - Aisyah, Siti; Khotimah, Iin Khusnul; Rahmawati, Hafni (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The community service team created the best boba formula through research and presented it to community service partners at Conac Snacks and Drinks Banjarbaru Student Business Group. Boba tilapia seaweed is considered to have a higher nutritional value than other boba available on the market. The service activity aims to provide the Conac Student Business Group with science and technology transfer for processing tilapia fish into flour and seaweed dry into seaweed porridge and boba tilapia seaweed products and modern drinks variations using boba toppings. This will increase the variety of beverage business products and increase profits. Technology transfer was practiced by introducing processed boba made from tilapia and seaweed along with a range of beverages, such as boba milk tea and chocolate milo. This was demonstrated by the boba's excellent texture, taste, odor, and color. A more thorough examination of the seaweed boba fish processing industry was done. Three techniques were used to carry out the activity: business approaches and assistance, demonstrations of how to process milk tea boba tilapia seaweed, and counseling regarding the procedure. The judges found the milk tea boba made from tilapia and seaweed to be tasty, nutritious, and of excellent quality as a result of this activity. A profit of IDR 45,000 was made during one production period, according to an analysis of the boba tilapia seaweed company; therefore, it is envisaged that it will enable the Conac Snacks and Drinks Banjarbaru Student Business Group to generate more revenue and sales.